EVALUATION OF THE EFFICIENCY OF PHYTOTHERAPY WITH MASTODINONE AND GELARIUM IN PATIENTS WITH DIFFUSE FORMS OF MASTOPATHIES - N. I. Rozhkova; Ye. V. Meskikh (Опухоли женской репродуктивной системы)
The authors define mastopathies and consider the major forms of this disease. They also present the results of the clinical trials eval- uating the efficiency of the herbal drugs mastodinone and gelarium in different forms of diffuse mastopathies, accompanied by the pain syndrome of varying degree, and depression.